Analisis Sistem Pengereman Singaperbangsa Electric Vehicle - Shendy Atmaja; Iwan Nugraha Gusniar; Arifin (Jurnal Serambi Engineering, 2024)
Electric cars are vehicles that use an electric motor as the main source of power to move the vehicle. In an electric car, braking is also required. The braking that is usually used in competitions is how the braking is maximal or not maximal during a raceover a predetermined distance, and there are many different types of braking that are used, some of which use disc brakes. Therefore, a test was carried out on the influence of speed on braking results in electric cars. The aim of this research is to investigate the effect of speed on the braking results of the Singaperbangsa Electric Vehicle Bersama electric car over a predetermined distance. To determine the effect of speed on braking results, researchers carried out tests by carrying out braking tests with a predetermined track distance of 15 meters with speed variations of 30 km/hour, 40 km/hour and 50 km/hour.